THE IMPLEMENTATION OF EXTENSIVE READING AND EXTENSIVE LISTENING IN XREADING AS ENGLISH LEARNING APPROACH - Eko Windu Prasetya; Ayu Rini Tri Utari; Helta Anggia; Yulan Puspita Rini (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2021)
This research is based on the implementation of ER and EL in Xreading as the 1st semester students’ English learning approach. The population of this research is students of English Education, Universitas Bandar Lampung. This research aimed to know how the principles of extensive reading and extensive listening implemented in ER and EL process through Xreading website and what students' perceptions of the implementation of ER and EL in Xreading as the 1st semester students’ English learning approach. The instruments of this research were observation, interview and TOEL test. Then, the data were analyzed by coding compression. The result showed that most of the ER principles had been implemented well in the implementation of ER in Xreading. On the other side, the implementation of EL in Xreading, only several principles of EL have been implemented. Thus, the implementation of the ER process in Xreading was more dominated than the EL process. Even though EL also helped students to learn the pronunciation of words. But, the students did not implement principles of EL optimally. Consequently, ER in Xreading was suitable for the 1st semester students’ English learning approach, but EL in Xreading was not suitable for the 1st semester students’ English learning approach. During the ER and EL process in Xreading, students preferred reading to listening to the material.